Estudio de factibilidad para el desarrollo de nuevos mercados en la provincia de Los Ríos por parte de la empresa Agrimen S.A. de la ciudad de Ventanas, año 2012 - Rizzo Loor, Martha Lizbeth (2013)
The feasibility study for the development of new markets for the company Agrimen SA, aims to participate in the canton Windows and its catchment area comprised Puebloviejo, Urdaneta, Vinces and Palenque, through a proposal to create jobs, added value and contribute to the development of agricultural production. The 52.66% of the inhabitants of the area of influence of the corner windows would be willing to make purchases in a new agrochemical company, as long as this has all the inputs. Also through field research it was determined that 80.05% agreed that the agency is installed in this county. During the ten years of operation will create three jobs. For opening new markets by Agrimen S.A., and in relation to the unmet demand, aspirational address in the first year to 1% of the hectares of the area of influence of the corner windows in the first year, 2% in the second year and 3% from the third year onwards. The financial indicator results obtained are as follows: Net Present Value (NPV) + $ 62,811,281, Internal Rate of Return (IRR) 311.03%, Benefit Cost Ratio (Rb/ c) 1.51, showing that this research is viable. This project represents an option to improve the productivity of the area of influence because of the input costs and the availability of them in the agency will implement Agrimen S.A, canton Windows.